The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1017/s0031182013001169
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the three main clonalToxoplasma gondiilineages from wild mammalian carnivores in the UK

Abstract: Toxoplasma gondii is a zoonotic pathogen defined by three main clonal lineages (types I, II, III), of which type II is most common in Europe. Very few data exist on the prevalence and genotypes of T. gondii in the UK. Wildlife can act as sentinel species for T. gondii genotypes present in the environment, which may subsequently be transmitted to livestock and humans. DNA was extracted from tissue samples of wild British carnivores, including 99 ferrets, 83 red foxes, 70 polecats, 65 mink, 64 badgers and 9 stoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 35 publications
(51 reference statements)
2
42
0
Order By: Relevance
“…In France, T. gondii was isolated from 9 of 14 seropositive red foxes [40], whereas in the UK, only 6.0% of foxes were PCR positive and type II lineage was demonstrated [36]. A study on T. gondii prevalence in minks in the UK [36] showed similar results to those obtained in the current study (20% and 25%, respectively), whereas in Chile, T. gondii DNA was demonstrated only in one of 73 American minks [41].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In France, T. gondii was isolated from 9 of 14 seropositive red foxes [40], whereas in the UK, only 6.0% of foxes were PCR positive and type II lineage was demonstrated [36]. A study on T. gondii prevalence in minks in the UK [36] showed similar results to those obtained in the current study (20% and 25%, respectively), whereas in Chile, T. gondii DNA was demonstrated only in one of 73 American minks [41].…”
Section: Discussionsupporting
confidence: 82%
“…In another study in Poland, T. gondii DNA was found, depending on the methods used, in 13.8-19% of red foxes, 25-32% of badgers, 24-29% of raccoon dogs and 28-33% of martens [35]. In the UK, the presence of T. gondii DNA in brains collected from wild carnivores was detected in 19 of 65 Eurasian badgers (29.2%) [36]. In the Czech Republic, Turčeková et al [27] showed a high T. gondii prevalence in martens (50%), in which revealed genotypes II and III.…”
Section: Discussionmentioning
confidence: 96%
“…gondii , examined by semi-nested PCR, with 8.8% (n = 17) in Jilin province and 8.5% (n = 19) in Hebei province. The prevalence was lower comparing to other studies, such as the 13.9% in farmed minks in Poland by latex agglutination test (LAT) [21], 29.2% in feral minks in UK by PCR [22], 66% in feral minks in USA by the Sabin-Feldman dye test [23], 70% in minks in Chile by LAT [24] and 77% in minks in USA by MAT [25]. The difference may due to the different living environment, regions, the density of felids, the diet of minks and different sensitivity and specificity of detection methods, and the DNA prevalence only reflects prevalence in 2 farms of the two provinces.…”
Section: Resultsmentioning
confidence: 56%
“…gondii isolates in mink was limited worldwide, to our knowledge, only one document recorded that Type II of T . gondii isolates was found in feral mink in the UK [22] using 5 genetic markers (5' SAG2, 3' SAG2, SAG3, GRA6, BTUB). In China, until the present study, there was no information concerning genetic characterization of T .…”
Section: Resultsmentioning
confidence: 99%
“…Although the Eurasian badger is classified as a carnivore; these animals also feed on a wide variety of plants (4). In some previous studies conducted in Europe, toxoplasmosis was detected in Eurasian badger using serological methods and/or conventional or nested polymerase chain reaction (PCR) methods (5)(6)(7)(8)(9)(10). In this study, using real-time PCR, we aimed to investigate the presence of T. gondii in a Eurasian badger that was found dead in the wildlife area of İzmir located in the Aegean region of Turkey.…”
Section: Introductionmentioning
confidence: 99%